ANALISA KAITAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN DAN POLITIK DENGAN VOLATILITAS HARGA SAHAM (Jurnal Ekonomi : Journal of Economic, 2022)
AbstractThe researcher investigates the relationship between stock price volatility and politics with sustainability reports. Sustainability report in this study is focused on the level of disclosure which company shares as well as on the political side focused on the general election. The research was conducted using three industrial sectors on the stock exchange which were indicated to have a direct influence on the materials for preparing the sustainability report. Using environmental, social and government scores from Bloomberg and stock prices from 32 companies that were sampled during the 2015 to 2020 period. By using hypothesis testing through multiple regression analysis as a method to find evidence of the relationship between the objects studied. The fact that disclosure of sustainability reports negatively affects stock price volatility, which mean the higher percentage of sustainability report disclosures will reduce stock price volatility which will linearly reduce the risk of investors in investing in companies with good or high levels of disclosure. Furthermore, the researchers found that politics did not have relationship with stock price volatility. Management may consider sustainability report disclosure with specified criteria to attract investors. On the other hand, investors and shareholders can consider sustainability reports as one of the investment selection criteria.Keywords:    environment; government; political; social; stock price volatility; sustainability report.